2009
DOI: 10.1007/s11064-009-0100-z
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Expression of Proteins Involved in Iron Homeostasis in Brain Regions is Altered by Age and by Iron Overloading in the Neonatal Period

Abstract: Abnormally high levels of iron are observed in the brain of patients suffering from neurodegenerative disorders. The mechanisms involved in iron accumulation in neurodegenerative disorders remain poorly understood. In the present study we investigated the effects of aging and neonatal iron overload on the mRNA expression of proteins critically involved in controlling iron homeostasis. Wistar rat pups received a single daily dose of vehicle or iron (10 mg/kg of b.w. of Fe(2+)), at postnatal days 12-14. The expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…Iron supplementation of the diet of neo natal rodents causes a permanent increase in iron levels in the brain, 48-50 alters expression of proteins involved in iron homeostasis, 51 decreases neuronal counts, increases astrogliosis, 52,53 and leads to motor and cognitive abnormalities in adulthood. 48,49 These findings suggest that the infant brain is less protected against systemic iron overload than is the adult brain.…”
Section: Box 2 | Evolution Of Iron Regulatory Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron supplementation of the diet of neo natal rodents causes a permanent increase in iron levels in the brain, 48-50 alters expression of proteins involved in iron homeostasis, 51 decreases neuronal counts, increases astrogliosis, 52,53 and leads to motor and cognitive abnormalities in adulthood. 48,49 These findings suggest that the infant brain is less protected against systemic iron overload than is the adult brain.…”
Section: Box 2 | Evolution Of Iron Regulatory Mechanismsmentioning
confidence: 99%
“…No increase in iron levels in the brain at 10 weeks 10 weeks is a relatively young age to consider the effects of iron in the brain in relation to age-related neurodegeneration Acikoyl et al 51 Analysis of non-haem iron levels in the brains of TFR2 -/-mice aged 10 weeks…”
Section: Contribution Of Early-life Exposurementioning
confidence: 99%
“…The design and development of fluorescence sensors for the detection of Fe 3+ is becoming an important issue because of the vital roles Fe 3+ plays in environmental, biological, and chemical systems [1][2][3][4][5]. Recently, a large number of fluorescent chemosensors were exploited as useful tools for the detection of Fe 3+ owing to their intrinsic sensitivity, selectivity, and capacity for rapid, real-time monitoring [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Although brain maturation in mice is quite different from that in human infants, the authors proposed that elevated neonatal iron intake may be a potential risk factor for later development of Parkinson disease. That early life iron exposure can have long-term consequences for brain iron homeostasis was shown by Dornelles et al (36) who analyzed the gene expression of transferrin receptor, H-ferritin, and iron regulatory protein 2 in the cortex, hippocampus, and striatum of rats who had been given 10 mg ferrous iron/kg body weight during PDs 12-14 when they were 15-d, 90-d, and 2-y old. All of these proteins that are involved in iron homeostasis regulation were dysregulated by early iron exposure, and the authors suggested that this involvement may explain the misregulation shown in neurologic disorders.…”
Section: Effects Of Iron Excess On Cognitive Devel-opment Of Iron-repmentioning
confidence: 97%